A lenição do tepe alveolar intervocálico por falantes do português brasileiro - Wellington Araujo Mendes Junior (2018)
The aim of this dissertation is to analyze the phenomenon known as intervocalic tap lenition, as it occurs in Brazilian Portuguese (BP). Examples of this phenomenon include the variation observed in para [pa.] ~ [pa] or in brasileiro [ba.zi.lej.] ~ [ba.zi.lej.]. The corpus was collected through the website www.fonologia.org and it is made up of speech recordings resulting from the reading of a text from the project Sibilants and Rhotics of Brazilian Portuguese, process: 484590 / 2013-8, Universal Call for Proposals of CNPq. Since tap lenition is an optional phenomenon in BP, this dissertation seeks to evaluate which conditions favor or inhibit the process and it also aims to evaluate whether tap loss is gradient or abrupt. These investigations were mainly based on the assumptions of the Exemplar Theory (JOHNSON, 1997; JOHNSON, MULLENIX, 1997; PIERREHUMBERT, 2001). The fundamental theoretical target was to present reflections on the consequences of segmental loss for phonological representations. In order to investigate such phenomenon, two data analyses were performed: the categorical and the acoustic one. The categorical analysis evaluated the variables (1) tonicity, (2) number of syllables, (3) adjacent vowels, (4) lexical frequency, (5) lexical item, (6) sex, (7) individual and (9) geographical border. The data was submitted to the statistical program R (R CORE TEAM, 2013) and the following factors were significant in the statistical model: tonicity, number of syllables, following vowel, lexical frequency and geographical boarder. The acoustic analysis evaluated how tap lenition takes place in a gradient manner. We analyzed the duration of taps and adjacent vowels in relation to the events of tap occurrence, tap absence and gradient lenition. The objective was to evaluate whether segmental loss of the tap implies in temporal word loss or in temporal loss of the adjacent vowels. The results of the acoustic analysis pointed to a temporal, articulatory and acoustic reorganization of the words and of the VV sequences involved in tap lenition. Articulatorily, there is a constant decrease of the constriction usually observed within canonical taps. Acoustically, the tap presents characteristics of other segments as it is reduced: not only of approximants but also of vowels. Temporally, there are changes involved in the lexical level - such as temporal word loss when the tap does not manifest itself - and in the segmental level, such as temporal gain of the vowels of reduced VV sequences. The hints of gradient reduction shown in this research corroborate the premises of the Exemplar Theory regarding the gradiency of linguistic change phenomena.